Histone deacetylase inhibitors in cancer: What have we learned?. Issue 8 (23rd December 2014) - Whittle, James R.; Desai, Jayesh
<x xml:space="preserve">Abstract</x> The authors outline the current stage in the development of histone deacetylase inhibitors in solid tumors. Despite single‐agent benefit in a small number of hematologic malignancies, evidence in solid organ cancers suggests that outcomes will be more promising with combination therapy and should be the focus of future studies.